Combating fuel-driven aqua-pollution using "benzomagnets". Issue 20 (21st February 2017) - Seddigi, Zaki S.; Ahmed, Saleh A.; Sardar, Samim; Yarkandi, Naeema H.; Abdulaziz, Mohammed; Pal, Samir Kumar
Abstract : "Benzomagnets" were developed using protoporphyrin IX-sensitized TiO2 microspheres to monitor and combat fuel-driven aqua-pollution. Abstract : Marine environments are frequently exposed to semi-volatile polyaromatic hydrocarbons (PAHs) from anthropogenic sources including the incomplete combustion of fossil fuels or oil spills. Benzo[ a ]pyrene (BP), one of the most dangerous PAHs, has been found to be the champion killer of marine life due to its potent mutagenicity and carcinogenicity. Herein, we developed a novel porous microsphere comprising a nanohybrid of TiO2 nanoparticles (∼20 nm diameter) and a biologically relevant dye (protoporphyrin IX) for the complete removal of BP from aqueous environments. Steady state/picosecond-resolved spectroscopy and high-resolution electron microscopy were used for the structural characterization of the functional microspheres (FMs). The FMs were found to adsorb the dispersed BP with almost cent percent efficiency for several cycles with photo/chemical recharging options. We deposited the FMs onto a stainless steel mesh to fabricate a prototype for future marine application in the real-world removal of pollution. We also designed an assessment strip using the FMs for the rapid onboard monitoring of BP contamination in any aqueous environment, which was found to detect ppm (25 micromolar) and ppt (50 picomolar) levels of BP using absorption and fluorometric assays, respectively.